ANALISIS PENGARUH RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS)DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2017-2019) - Dewi Anggraini (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
In capital market activities, investors need accurate information so that investors are not trapped in adverse conditions because investing in the stock exchange is a type of investment with relatively high risk, although it promises a relatively large profit. The information needed is to know what variables that influence the occurrence of fluctuations in stock prices and also to find out how the relationship between these variables. The purpose of this study was to determine the effect of Return On Equity (ROE), Earning Per Share (EPS) and Net Profit Margin (NPM) on stock prices in the consumer goods industry sector. This study uses secondary data from third-party publications and the research method used is purposive sampling with an observation period of 2017-2019 with the number of samples obtained by 32 companies per year. The data analysis technique used is descriptive statistical analysis. Test requirements analysis using the normality test. The classic assumption test in this research uses multicollinearity test, autocorrelation test, and heteroscedasticity test. Data analysis used multiple linear regression analysis, partial test (t test), simultaneous test (F test), and coefficient of determination (R2). Based on the results of research using multiple linear regression analysis with the t test obtained ROE has a positive and significant effect on stock prices, EPS has a positive and significant effect on stock prices and NPM has a negative and not significant effect on stock prices. From the F test obtained ROE, EPS and NPM simultaneously there is a significant influence on stock prices.